Inventário turístico: Acari/RN - Edição 2022 - 2023 - Taveira (Coord.), Marcelo da Silva (2023)
The municipality of Acari is located in the Central Potiguar mesoregion and in the Seridó Oriental microregion, at a distance of 215 km from the capital of Rio Grande do Norte, Natal, integrating the Seridó Tourism Pole (regional governance instance of Rio Grande do Norte ). Acari has significant tourist potential, its historical relevance for the region, being one of the first cities to be built in the Potiguar Seridó, taking the title of the cleanest city in Brazil. In addition, the municipality is part of the Seridó Geopark, featuring four geosites: Poço do Arroz, Cruzeiro, Marmitas do Rio Carnaúba, and Açude Gargalheiras with its 40,000,000 cubic meters, being one of the most visited attractions in the municipality, considered one of the tourist wonders of Rio Grande do Norte. The municipality still stands out with its architectural complexes, gastronomy and handicrafts, in addition to its religiosity, arising from the devotion to the patron saint Nossa Senhora da Guia and its economy, driven by sewing workshops and tourism, one of the main economic activities in the municipality today. . Given these impressions, it is necessary to delve into the tourist potential of Acari, through a methodology created by professors and students from FELCS/UFRN and the Laboratory of Research and Tourism Studies (LAPET), gathering information that cover the municipal context. Thus, the referred document provides data from the following categories: a) Tourism Support Infrastructure; b) Tourist Services and Equipment; c) Tourist attractions; d) Tourist trade; e) Commercial Activities to Support Tourism. The tourist inventory is the first step in planning tourist activity in a locality, as it has quantitative data and qualitative information that will help municipal public management to create actions for tourism to develop in an integrated and sustainable way.